Prospects of Regional Cooperation Railway System in Central Asian Countries - Aminboyevich, Radjabov Ozodbek (European Journal of Life Safety and Stability (2660-9630), 2023)
Limited natural resources, internal socio-economic and political crises, and the low level of infrastructure development, especially in the first years after gaining sovereignty, have affected the trade, transport, and logistics vulnerability of Central Asian countries. Trade between the People’s Republic of China and European countries became a determining factor in developing the region’s transport routes. More than 90 % of freight is delivered by sea, but the role of land routes has increased significantly since 2020. China faces the pressing issues of developing the economies of its western provinces, especially the Xinjiang Uygur Autonomous Region.